18F‐sodium fluoride positron emission tomography of the racing Thoroughbred fetlock: Validation and comparison with other imaging modalities in nine horses. (28th September 2018) - Spriet, M.; Espinosa‐Mur, P.; Cissell, D. D.; Phillips, K. L.; Arino‐Estrada, G.; Beylin, D.; Stepanov, P.; Katzman, S. A.; Galuppo, L. D.; Garcia‐Nolen, T.; Murphy, B.; Stover, S. M.
Summary: Background: Early and accurate detection of stress remodelling in racehorses is of utmost importance to prevent catastrophic injuries. Current imaging techniques have limitations in assessing early changes predisposing to catastrophic breakdowns. Positron emission tomography (PET) using 18 F‐sodium fluoride ( 18 F‐NaF) is a sensitive method for the detection of early bone turnover and may improve early recognition of subtle injuries. Objectives: To validate the clinical use of 18 F‐NaF PET in Thoroughbred racehorses, to assess the value of PET in the detection of bone lesions and to compare PET results with findings of other advanced imaging modalities, clinical examination and pathology. Study design: Experimental exploratory study. Methods: Twenty fetlocks from nine Thoroughbred racehorses were imaged using 18 F‐NaF PET, computed tomography (CT) and scintigraphy. Five fetlocks were also imaged with magnetic resonance imaging and four fetlocks were also examined histologically. Imaging findings were independently reviewed by three board certified radiologists. Imaging, clinical and histopathological findings were correlated. Results: PET imaging was well‐tolerated by all horses. PET detected focal areas of 18 F‐NaF uptake in instances where other imaging modalities did not identify abnormalities, in particular in the proximal sesamoid bones. Maximal standardised uptake values could be measured to quantify the activity of lesions. Areas of 18 F‐NaF uptake corresponded to regions of increased vascularity and increased osteoblastic activity. Main limitations: Limited number of cases. Conclusions: 18 F‐NaF PET imaging of the Thoroughbred fetlock is feasible and compares favourably with other imaging modalities in detecting stress remodelling in Thoroughbred racehorses. PET appears to be a beneficial imaging modality when used for early detection of stress remodelling in an effort to prevent catastrophic musculoskeletal injuries in this population of horses.